Factors contributing to the low morale of officials in the Department of Correctional Services : an employee assistance programme perspective - stephaniepiek@vodamail.co.za (University of Pretoria, 2013)
Dissertation (MSW (Employee Assistance Programme))--University of Pretoria, 2008.